2018
DOI: 10.1093/ecco-jcc/jjy006
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Risk of Inflammatory Bowel Disease-associated Colorectal Neoplasia with Use of Thiopurines: a Systematic Review and Meta-analysis

Abstract: This study demonstrated that thiopurine use was associated with a reduced risk of colorectal neoplasia, advanced neoplasia and CRC in IBD patients, especially those with long disease duration [> 8 years].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 83 publications
1
42
1
Order By: Relevance
“…Although the focus of this study was on the incidence and prevalence of inflammatory bowel disease and the risk of mortality and colorectal cancer in these populations, a significant limitation is in identification of inflammatory bowel disease phenotype. It has previously been shown that disease severity, extent and comorbid primary sclerosing cholangitis are significant factors in the risk of colorectal cancer in inflammatory bowel disease 6,50 . This study has considered all Crohn's disease and all ulcerative colitis as single diseases and the paucity of data in THIN regarding inflammatory bowel disease phenotypic subtypes would not permit a more in‐depth analysis of how these factors affect colorectal cancer and mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…Although the focus of this study was on the incidence and prevalence of inflammatory bowel disease and the risk of mortality and colorectal cancer in these populations, a significant limitation is in identification of inflammatory bowel disease phenotype. It has previously been shown that disease severity, extent and comorbid primary sclerosing cholangitis are significant factors in the risk of colorectal cancer in inflammatory bowel disease 6,50 . This study has considered all Crohn's disease and all ulcerative colitis as single diseases and the paucity of data in THIN regarding inflammatory bowel disease phenotypic subtypes would not permit a more in‐depth analysis of how these factors affect colorectal cancer and mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…A 2018 meta-analysis by Zhu et al reinforced the antineoplastic activity of thiopurine-based immunomodulators, with an odds ratio of 0.51 for HGD and 0.55 for CRC. 15 Rates of immunomodulator and biologic use in CD were higher, although nearly half (47% (n = 8, CI 26-69%) only received a biologic for 6 months or less prior to the neoplasia diagnosis. While there are few long-term data regarding CRC risk reduction with anti-TNF agents, a 2011 Dutch case-control study of 173 cases of IBD-associated CRC found a significant reduction in CRC risk with the use of infliximab, with an odds ratio of 0.09.…”
Section: Discussionmentioning
confidence: 92%
“…[1][2][3][4] The incidence, although variably reported, is believed to be as high as 18% in ulcerative colitis (UC) and 8.3% in Crohn's disease (CD) after a disease duration of 30 years. 5,6 The median age of onset of CRC in IBD is as young as 43 years, up to [15][16][17][18][19][20] years earlier than that of sporadic CRC. 5 The prognosis is poor, with an overall 5-year survival of 33-55% for UC-associated and 18-46% for CD-associated CRC.…”
Section: Introductionmentioning
confidence: 99%
“…The first benefit of 5‐ASA appears to relate to control of colonic inflammation, and therefore as expected is not specific to 5‐ASA. A recent systematic review and meta‐analysis of 27 studies involving 95 937 patients with IBD demonstrated that thiopurine use was associated with a reduced risk of both high‐grade dysplasia and CRC, particularly among those with a longer disease duration, 65 although the risk reduction appeared limited to those with UC in a separate meta‐analysis 66 . The second potential benefit relates to the postulated direct chemopreventive effects of 5‐ASA, with studies suggesting a range of relevant biological mechanisms including cell checkpoint activation, 67 improvement of DNA replication fidelity, 68 scavenging of reactive oxygen and nitrogen species 69 and interference with Wnt/beta‐catenin signalling 70 .…”
Section: The Role Of 5‐asa In Crc Prevention—a Key Consideration?mentioning
confidence: 99%